2021
DOI: 10.3390/cells10082097
|View full text |Cite
|
Sign up to set email alerts
|

Development of the BioHybrid Assay: Combining Primary Human Vascular Smooth Muscle Cells and Blood to Measure Vascular Calcification Propensity

Abstract: Background: Vascular calcification is an active process that increases cardiovascular disease (CVD) risk. There is still no consensus on an appropriate biomarker for vascular calcification. We reasoned that the biomarker for vascular calcification is the collection of all blood components that can be sensed and integrated into a calcification response by human vascular smooth muscle cells (hVSMCs). Methods: We developed a new cell-based high-content assay, the BioHybrid assay, to measure in vitro calcification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Potential further applications of the described method include patients' serum screening for in vitro calcification development as a surrogate marker for personalized development of vascular calcification. The platform has demonstrated its sensitivity toward dialysis and vitamin K treatment, in addition to both metabolic and non-metabolic diseases that are linked to patients with poor cardiovascular status and prognosis 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential further applications of the described method include patients' serum screening for in vitro calcification development as a surrogate marker for personalized development of vascular calcification. The platform has demonstrated its sensitivity toward dialysis and vitamin K treatment, in addition to both metabolic and non-metabolic diseases that are linked to patients with poor cardiovascular status and prognosis 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we detail the method for the application of a novel assay that utilizes hVSMCs with a fluorescent imaging probe to determine in vitro VC progression as well as function as a singular end-stage calcification assay. We previously demonstrated that this assay is directly comparable to the o-cresolphthalein and Alizarin Red methods and can be used to distinguish between varying culture conditions 20 . In addition to real-time measurements, this assay may be used to determine the propensity of serum or plasma samples as a surrogate marker for clinical VC development 20 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Accordingly, mice lacking the functional fetuin-A gene develop severe soft tissue mineralization starting in the lumen of microvasculature and have impaired bone formation [10][11][12][13]. Previously we showed that fluorescent derivatives of the mineral-binding protein fetuin-A/α2-Heremans-Schmid glycoprotein (Ahsg) serve as sensitive and specific reagents to detect early-stage calcifications ex vivo and in vivo [13][14][15][16]. We hypothesized that the mineral binding properties of fetuin-A might be improved by optimizing the protein-mineral binding interface.…”
Section: Introductionmentioning
confidence: 99%
“…did not consider the impact of renal replacement therapy on IL-6, did not test the level of vitamin K, did not mention whether CKD patients were taking vitamin K antagonists, such as warfarin, and did not conduct subgroup analysis of peritoneal dialysis patients and HD patients. Maybe the BioHybrid assay [ 7 ], a new cell-based high-content assay, to measure the vascular calcification propensity of an individual should be widely used.…”
mentioning
confidence: 99%